Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/19371918.2015.1137517
|View full text |Cite|
|
Sign up to set email alerts
|

Gender and Women Development Initiatives in Bangladesh: A Study of Rural Mother Center

Abstract: Women-focused development initiatives have become a controversial issue connected with women's health and welfare. Previous studies indicated that development initiatives might increase women's workload, family conflict, and marital violence. This study explored the gendered characteristics of a development initiative Rural Mother Center in Bangladesh. Data incorporated policy document and interviews of social workers working with the mother centers in two northwest subdistricts. The qualitative content analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Finally, although Bangladesh is emerging as a low-middle income country, rural poverty is still a major problem and rural women lack opportunity for education, lack independence and lack access to property [21, 72, 73]. More interventions for women’s social development are needed to build skill and capacity for women so that they can advance to more rewarding positions in industrial enterprises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although Bangladesh is emerging as a low-middle income country, rural poverty is still a major problem and rural women lack opportunity for education, lack independence and lack access to property [21, 72, 73]. More interventions for women’s social development are needed to build skill and capacity for women so that they can advance to more rewarding positions in industrial enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…However, the women who participate in unskilled work are at risk of adverse effects on their health and well-being due to the work environment and demands associated with this changing gender role [21]. Studies have found that participation in paid work increases women’s workload, family conflicts, and their vulnerability to male marital violence [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…A study also reported that 81% of all loans given to these women are controlled by their husbands ( Karim & Law, 2013 ). Previous studies further speculate that female participation in development initiatives may be limited by patriarchal gender norms in rural Bangladesh, by a lack of woman-friendly market facilities, by a view where all women are seen as necessarily to be entrepreneurs, and by a lack of transformative policies on gender ( Karim, Emmelin, Lindberg, & Wamala, 2016 ; Karim & Law, 2013 ).…”
Section: Gender Inequality and Female-focused Development In Rural Bamentioning
confidence: 99%
“…However, 98.6% of male migrants had worked in income generating activities during the previous 12 months, and among the unemployed, 67.1% had migrated for work. There is a distinctive pattern between men and women looking for work and finding it, one that is rather common in the Bangladeshi patriarchal society where men are the primary earners in the family (Parveen, 2007;Karim et al, 2016;Biswas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%